Proposed Determination of Work Criteria Standards on OMAX Ratio Performance to Increase Productivity - Umi Tri Utami; Utaminingsih Linarti; Annie Purwani; Susanto Sudiro (Jurnal Ilmiah Teknik Industri, 2022)
This study focuses on measuring the productivity of PT.X, especially the welding and painting unit, based on the total realization of production, several employees, working hours, overtime hours, and lost hours of employees. The purpose of this study is to propose a strategy for improving the productivity ratio of the welding and painting unit, which is still below the standard by setting performance criteria standards. The method used is the objective matrix (OMAX) and root cause analysis (RCA) which is carried out using six ratios of productivity measurement and looking for the root cause of the ratio at a level below the standard. The results show that three ratios are still below the standard of the six productivity measurement ratios, such as ratios 2, 3, and 5. These ratios need to be improved by increasing the realization of production results, reducing the number of absent workers, and reducing the total working hours of employees every month. Based on the study results, improvements in the three ratios were able to increase the productivity index of PT.X's welding and painting units.